1995
DOI: 10.1097/00000539-199507000-00013
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of N-Methyl-D-aspartate Antagonist (Ketamine) on Single and Repeated Nociceptive Stimuli

Abstract: Ketamine is a noncompetitive N-methyl-D-aspartate (NMDA) receptor channel blocker known to inhibit "wind-up" and hence central hyperexcitability of dorsal horn neurons. We sought to assess the effect of ketamine on single and repeated nociceptive stimuli. A placebo-controlled, human (12 volunteers) experimental study was conducted in which several psychophysical (pain detection and tolerance thresholds, magnitude ratings) and electrophysiologic (withdrawal reflex) techniques were used 1) to investigate whether… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
116
2
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(127 citation statements)
references
References 21 publications
7
116
2
2
Order By: Relevance
“…In the current study, ketamine, the active control, attenuated the TS pain detection threshold and pain following suprathreshold TS stimulation in humans as expected, 8,9 showing the importance of the NMDA receptor for mediating central integration in humans.…”
Section: The Human Model Of Temporal Summationsupporting
confidence: 80%
See 2 more Smart Citations
“…In the current study, ketamine, the active control, attenuated the TS pain detection threshold and pain following suprathreshold TS stimulation in humans as expected, 8,9 showing the importance of the NMDA receptor for mediating central integration in humans.…”
Section: The Human Model Of Temporal Summationsupporting
confidence: 80%
“…A loading dose of ketamine of 0.5 mg/kg was used, followed by infusion of 9 Kg/kg per minute for 20 minutes. 8 Ketamine was not administered after pregabalin dosing because of the potential of a carryover effect from pregabalin; therefore, only the placebo infusion was administered after oral pregabalin dosing. Subjects attended the clinic on 6 separate occasions: screening; training session; at study periods 1, 2, and 3; and follow-up.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…No exact corresponding test is described in the literature. Arendt-Nielsen et al 38 described the lack of effect of ketamine on high-intensity laser pulses as well as brief electrical pulses. Investigating the effects of ketamine on heat stimulation of short duration (2 seconds), Arendt-Nielsen et al 37 found reduction of pain intensity after infusion of ketamine compared with placebo.…”
Section: Discussionmentioning
confidence: 99%
“…14 This is interesting, as we have previously shown that drugs that affect central sensitization inhibit temporal summation. [15][16][17] As facilitated temporal summation is a feature in neuropathic pain patients, 18,19 temporal summation may be a biomarker of drug effects on neuropathic pain.…”
mentioning
confidence: 99%